Polyvinyl acetal resin, conductive paste, and multilayer ceramic capacitors

JP2026167652APending Publication Date: 2026-10-14SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026058587
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026167652000001
    Figure 2026167652000001
  • Figure 2026167652000002
    Figure 2026167652000002
  • Figure 2026167652000003
    Figure 2026167652000003
Patent Text Reader

Abstract

The present invention aims to provide a polyvinyl acetal resin capable of forming a conductive layer with excellent solvent solubility and low surface roughness while preventing sheet attack, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. [Solution] The solubility parameter calculated according to Fedors' method is 10.25 or less, and the constituent unit is represented by the following formula (1), and R in the following formula (1) 1 A polyvinyl acetal resin in which the hydrocarbon group has 4 to 20 carbon atoms. [Formula 1] JPEG2026167652000007.jpg34156
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyvinyl acetal resin, a conductive paste, and a multilayer ceramic capacitor.

Background Art

[0002] Multilayer electronic components such as multilayer circuit boards, multilayer coils, and multilayer ceramic capacitors are widely used, and among these, multilayer ceramic capacitors are generally manufactured through the following processes. First, ceramic raw material powder is added to a solution obtained by dissolving a binder resin such as a polyvinyl butyral resin or a poly(meth)acrylate ester-based resin in an organic solvent, and the mixture is uniformly mixed to obtain a ceramic slurry composition. This slurry composition is cast onto a support, volatile components such as the solvent are distilled off by heating or the like, and then the resulting product is peeled from the support to obtain a ceramic green sheet. Next, a plurality of the obtained ceramic green sheets each coated with a conductive paste for internal electrodes by screen printing or gravure printing are alternately stacked, and thermocompression bonded to produce a laminate. Thereafter, a treatment for thermally decomposing and removing the binder resin component and the like contained in the laminate, a so-called degreasing treatment, is performed, and a multilayer ceramic capacitor is obtained through a step of sintering external electrodes on the end faces of a ceramic sintered body obtained by firing.

[0003] The conductive paste for internal electrodes is obtained by kneading conductive powder, an organic solvent, and a binder resin. As the above binder resin, ethyl cellulose and polyvinyl acetal resin are used. However, when a polyvinyl acetal resin is used as the above binder resin, there is a problem that stringing occurs when the paste is printed by screen printing. Patent Document 1 discloses a conductive paste containing a carboxylic acid-modified polyvinyl acetal resin, an organic solvent, and conductive powder from the viewpoint of ameliorating the above problem. In addition, Patent Document 2 discloses a conductive paste containing a polyvinyl acetal resin having an ethylene group from the viewpoint of ameliorating the above problem. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2017-228780 [Patent Document 2] Japanese Patent Publication No. 2008-285590 [Overview of the project] [Problems that the invention aims to solve]

[0005] In recent years, miniaturization of multilayer ceramic capacitors has attracted attention. However, the organic solvents currently used in the conductive paste for the internal electrodes remain on the ceramic green sheet during coating, dissolving the binder resin contained in the ceramic green sheet (so-called sheet attack). This results in holes and wrinkles in the ceramic layer, making it impossible to obtain the desired electrical properties. Furthermore, there is also the problem of not being able to obtain the desired surface properties when a conductive layer is formed.

[0006] The present invention aims to provide a polyvinyl acetal resin capable of forming a conductive layer with excellent solvent solubility and low surface roughness while preventing the aforementioned sheet attack, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. [Means for solving the problem]

[0007] Disclosure 1 has a solubility parameter of 10.25 or less calculated according to Fedors' method, and has a constituent unit represented by the following formula (1), wherein R in formula (1) 1 It is a polyvinyl acetal resin in which the hydrocarbon group has 4 to 20 carbon atoms. [ka] Disclosure 2 states that when the solubility parameter is X and the content of the constituent unit represented by formula (1) is Y, 2 The polyvinyl acetal resin described in Disclosure 1 is wherein / X is 65 or more and 900 or less, and the average degree of polymerization is less than 2300. Disclosure 3 is a polyvinyl acetal resin according to Disclosure 1 or 2, wherein the hydroxyl group content is 8 mol% or more and 25 mol% or less. Disclosure 4 relates to the R in formula (1) above. 1 The polyvinyl acetal resin is according to any one of disclosures 1 to 3, wherein the hydrocarbon group is linear and has 6 to 20 carbon atoms. Disclosure 5 is a polyvinyl acetal resin according to any one of Disclosures 1 to 4, wherein the content of the constituent unit represented by formula (1) is 5 mol% or more and 80 mol% or less. Disclosure 6 is a polyvinyl acetal resin according to any one of Disclosures 1 to 5, wherein the total amount of acetal groups is 79 mol% or more. Disclosure 7 is a conductive paste containing a polyvinyl acetal resin as described in any of Disclosures 1 to 6, an organic solvent, a conductive powder, and a dispersion improver. Disclosure 8 is a multilayer ceramic capacitor made using the conductive paste described in Disclosure 7.

[0008] As a result of diligent research, the inventors have discovered that a polyvinyl acetal resin having a solubility parameter calculated by Fedors' method within a predetermined range and possessing predetermined structural units can form a conductive layer with excellent solvent solubility and low surface roughness while preventing sheet attack, thus completing the present invention.

[0009] A polyvinyl acetal resin according to one embodiment of the present invention has a solubility parameter (SP value) of 10.25 or less, calculated by Fedors' method. Having the above solubility parameter within this range results in excellent solubility in low-polarity solvents and suppresses sheet attack on the ceramic green sheet. A preferred upper limit for the above solubility parameter is 10.2, and a more preferred upper limit is 10.0. Furthermore, a preferred lower limit for the above solubility parameter is 9.4, and a more preferred lower limit is 9.6. By setting the value above these lower limits, solubility in solvents can be improved, and the surface roughness of the conductive layer can be improved. The above solubility parameters are calculated using Fedors' method (RFFedors, Polym.Eng.Sci.,14(2),147-154(1974)). In this invention, the solubility parameter is determined by first calculating the unit parameters of each constituent unit of the polyvinyl acetal resin according to Fedors' method, and then summing the values ​​corresponding to the content of each constituent unit.

[0010] The above solubility parameters can be adjusted by the method of the acetalization reaction (whether or not a dispersant is used) and reaction conditions (addition temperature of aldehyde and catalyst, holding temperature) when producing polyvinyl acetal resin, the amount of hydroxyl groups, the amount of acetal groups, the amount of acetyl groups, the structure of the acetal unit (number of carbon atoms in the alkyl group), and the type of modifying group. In particular, it is preferable to adjust the parameters by the amount of hydroxyl groups, the amount of acetal groups, and the structure of the acetal unit (number of carbon atoms in the alkyl group).

[0011] A polyvinyl acetal resin according to one aspect of the present invention has a constituent unit represented by the following formula (1), wherein R in the following formula (1) 1 However, it is a hydrocarbon group having 4 to 20 carbon atoms. Having such a hydrocarbon group allows for excellent solubility in low-polarity solvents, suppression of sheet attack on the ceramic green sheet, and improvement of the surface roughness of the conductive layer.

[0012] [ka]

[0013] The above R 1 The number of carbon atoms is preferably 5 or more. A more preferable lower limit for the number of carbon atoms is 6, a preferred upper limit is 15, and a more preferable upper limit is 10. Note that the above R 1 This may be a combination of two or more hydrocarbon groups with different numbers of carbon atoms. In that case, a combination of a carbon-6 group and a carbon-9 group is preferred.

[0014] As the hydrocarbon group having 4 to 20 carbon atoms, an alkyl group having 4 to 20 carbon atoms is preferred. Examples of alkyl groups having 4 to 20 carbon atoms include butyl group, pentyl group, hexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, nonadecyl group, eicosyl group, and the like.

[0015] The hydrocarbon group having 4 to 20 carbon atoms may be a linear alkyl group or a branched alkyl group. Examples of the linear alkyl groups mentioned above include n-butyl group, n-pentyl group, n-hexyl group, n-heptyl group, n-octyl group, n-nonyl group, n-decyl group, n-undecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, n-hexadecyl group, n-heptadecyl group, n-octadecyl group, n-nonadecyl group, and n-eicosyl group.

[0016] Examples of the branched alkyl groups mentioned above include isobutyl group, isopentyl group, neopentyl group, 1-methylhexyl group, 1-methylheptyl group, 1-methyloctyl group, 1-methylnonyl group, 1-methyldecyl group, 1-methylundecyl group, and 1-methyldodecyl group. Other examples include 1-methyltridecyl group, 1-methyltetradecyl group, 1-methylheptadecyl group, 1-methylhexadecyl group, 1-methylpentadecyl group, 1-methyloctadecyl group, and 1-methylnonadecyl group. Furthermore, examples include alkyl groups in which an alkyl group having two or more carbon atoms is substituted on the carbon atom at position 1 (for example, 1-ethyldecyl group, 1-propylnonyl group, 1-butyloctyl group, 1-pentylheptyl group, 1-octyldecyl group, etc.). Furthermore, in branched alkyl groups, the branching position is not limited to the carbon atom at position 1, but may be a carbon atom at position 2 or higher. For example, alkyl groups in which a methyl group is substituted at position 2 or higher include 2-methylundecyl, 3-methylundecyl, and 4-methylundecyl groups. Also, alkyl groups in which an alkyl group having 2 or more carbon atoms is substituted at position 2 or higher include, for example, 2-ethylhexyl, 2-ethylheptyl, 2-ethyloctyl, 2-ethylundecyl, 2-ethyloctadecyl, 2-propylundecyl, 2-butylundecyl, and 2-octylundecyl groups. In addition, 3-ethylundecyl, 4-ethyloctadecyl, 4-butyloctadecyl, and neodecyl groups are also examples.

[0017] In the present invention, the hydrocarbon group having 4 to 20 carbon atoms is preferably a linear alkyl group. In particular, R in formula (1) 1 It is preferable that the hydrocarbon group is linear and has 6 to 20 carbon atoms. Furthermore, the alkyl group having 4 to 20 carbon atoms may consist of two or more alkyl groups including a linear alkyl group and a branched alkyl group, or it may consist only of a linear alkyl group. Also, R in formula (1) below 1 This may be an alkyl group based on a bio-derived aldehyde having 4 or more carbon atoms.

[0018] The content of the structural unit represented by the above formula (1) in the polyvinyl acetal resin according to one aspect of the present invention has a preferred lower limit of 5 mol%, a more preferred lower limit of 12 mol%, a still more preferred lower limit of 28 mol%, a preferred upper limit of 80 mol%, a more preferred upper limit of 70 mol%, and a still more preferred upper limit of 55 mol%. Thereby, the solubility in low-polarity solvents is excellent, sheet attack on ceramic green sheets can be suppressed, and the surface roughness of the conductive layer can be improved. The content of the structural unit represented by the above formula (1) is 1 H-NMR and 13 C-NMR (nuclear magnetic resonance spectrum) is used for measurement.

[0019] The polyvinyl acetal resin according to one aspect of the present invention preferably further has an acetal unit represented by the following formula (2), which is different from the structural unit represented by the above formula (1). By having the acetal unit represented by the following formula (2), the solubility in solvents can be improved.

[0020]

Chemical Formula

[0021] Examples of the alkyl group having 1 to 3 carbon atoms for the above R 2 include a methyl group, an ethyl group, a propyl group and the like. The alkyl group having 1 to 3 carbon atoms for the above R 2 may be linear or branched.

[0022] In a polyvinyl acetal resin according to one embodiment of the present invention, the content of acetal units represented by formula (2) is preferably 12 mol%, more preferably 35 mol%, preferably 70 mol%, and more preferably 52 mol%. By keeping the content of acetal units represented by formula (2) within the above range, good solubility in solvents can be achieved. The content of acetal units represented by formula (2) is 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy).

[0023] In one embodiment of the present invention, when the polyvinyl acetal resin contains acetal units represented by formula (1) and acetal units represented by formula (2), the total content of these units is preferably 80 mol% at the lower limit, more preferably 85 mol% at the lower limit, preferably 92 mol% at the upper limit, and more preferably 90 mol% at the upper limit. By keeping the total content within the above range, excellent solubility in low-polarity solvents can be achieved, sheet attack on the ceramic green sheet can be suppressed, and the surface roughness of the conductive layer can be improved.

[0024] In one embodiment of the present invention, when the polyvinyl acetal resin contains acetal units represented by formula (1) and acetal units represented by formula (2), the ratio of the two (content of acetal units represented by formula (1) / content of acetal units represented by formula (2)) is preferably 0.07 or more and 6.7 or less, and more preferably 0.53 or more and 1.6 or less. By keeping the ratio within the above range, excellent solubility in low-polarity solvents can be achieved, sheet attack on the ceramic green sheet can be suppressed, and the surface roughness of the conductive layer can be improved.

[0025] In one embodiment of the present invention, the total amount of acetal groups (sum of all acetal units) in the polyvinyl acetal resin is preferably 79 mol% or more. By keeping the total amount of acetal groups within the above range, excellent solubility in low-polarity solvents can be achieved, sheet attack on the ceramic green sheet can be suppressed, and the surface roughness of the conductive layer can be improved. The preferred lower limit for the total amount of acetal groups is 80 mol%, a more preferred lower limit is 82 mol%, an even more preferred lower limit is 85 mol%, a preferred upper limit is 92 mol%, and a more preferred upper limit is 90 mol%. 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy). Furthermore, the content of the constituent unit represented by formula (1) relative to the total amount of acetal groups (content of the constituent unit represented by formula (1) / total amount of acetal groups) has a preferred lower limit of 0.05 and a preferred upper limit of 1.0.

[0026] A polyvinyl acetal resin according to one aspect of the present invention has constituent units having hydroxyl groups. In one embodiment of the present invention, the content of the above-mentioned hydroxyl group-containing structural units (hydroxyl group amount) in the polyvinyl acetal resin is preferably 8 mol% or more and 25 mol% or less. This provides excellent solubility in low-polarity solvents, suppresses sheet attack on the ceramic green sheet, and improves the surface roughness of the conductive layer. The more preferred lower limit for the amount of hydroxyl groups is 9.0 mol%, the more preferred upper limit is 20 mol%, the even more preferred lower limit is 9.5 mol%, and the even more preferred upper limit is 15 mol%. 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy). By keeping the amount of hydroxyl groups within the above range, excellent solubility in low-polarity solvents can be achieved, sheet attack on the ceramic green sheet can be suppressed, and the surface roughness of the conductive layer can be improved.

[0027] A polyvinyl acetal resin according to one aspect of the present invention has constituent units having acetyl groups. In one embodiment of the present invention, the preferred lower limit of the content of the constituent units having the acetyl group (amount of acetyl groups) in the polyvinyl acetal resin is 0.1 mol%, and the preferred upper limit is 10 mol%. By setting the amount of acetyl groups to 0.1 mol% or more, good solubility in the solvent can be achieved, and by setting the amount of acetyl groups to 10 mol% or less, good solubility in the solvent can be achieved. A more preferred lower limit of the amount of acetyl groups is 0.3 mol%, and a more preferred upper limit is 5 mol%. The above acetyl group 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy).

[0028] The polyvinyl acetal resin according to one aspect of the present invention may have constituent units having a carboxylic acid. In one embodiment of the present invention, the preferred lower limit of the content of the carboxylic acid-containing structural unit (carboxylic acid modification amount) in the polyvinyl acetal resin is 0.1 mol%, and the preferred upper limit is 10 mol%. By setting the amount of carboxylic acid groups to 0.1 mol% or more, the paste viscosity can be increased, and by setting the amount of carboxylic acid modification to 10 mol% or less, solubility in solvents can be improved. A more preferred lower limit of the amount of acetyl groups is 0.3 mol%, and a more preferred upper limit is 5 mol%. The above amount of carboxylic acid modification 1 H-NMR and 13 Measurements are performed using 1C-NMR (nuclear magnetic resonance spectroscopy). The carboxylic acid of the constituent unit having the above-mentioned carboxylic acid is not particularly limited, and examples include itaconic acid, crotonic acid, maleic acid, phthalic acid, etc.

[0029] If the solubility parameter is X and the content of the constituent unit represented by formula (1) is Y, then Y 2 / X is preferably 65 or more and 900 or less, more preferably 80 or more and 500 or less, and even more preferably 85 or more and 400 or less. The above Y 2By setting / X within the above range, excellent solubility in low-polarity solvents can be achieved, sheet attack on the ceramic green sheet can be suppressed, and the surface roughness of the conductive layer can be improved. Note that the above Y 2 / X can be adjusted by the method of the acetalization reaction when producing polyvinyl acetal resin (whether or not a dispersant is used), the reaction conditions (addition temperature of aldehyde and catalyst, holding temperature), the amount of hydroxyl groups, the amount of acetal groups, the amount of acetyl groups, the structure of the acetal unit (number of carbon atoms in the alkyl group) and its content, the type of modifying group, etc.

[0030] In one embodiment of the present invention, the polyvinyl acetal resin preferably has an average degree of polymerization of less than 2300. This makes it possible to form a conductive layer with excellent solvent solubility and low surface roughness while preventing sheet attack. In one embodiment of the present invention, the polyvinyl acetal resin has an average degree of polymerization of preferably 200 or more, and preferably less than 2300. An average degree of polymerization of 200 or more allows for good viscosity stability of the conductive paste and enables the formation of a conductive layer with low surface roughness. An average degree of polymerization of less than 2300 allows for excellent solubility in solvents and good viscosity stability of the conductive paste. More preferably, the average degree of polymerization is 700 or more, and more preferably less than 1800. The average degree of polymerization of the polyvinyl acetal resin can be determined from the polyvinyl alcohol used as a raw material.

[0031] A polyvinyl acetal resin according to one aspect of the present invention may be copolymerized with ethylenically unsaturated monomers, to the extent that the effects of the present invention are not impaired. The above ethylenically unsaturated monomers are not particularly limited and include, for example, acrylic acid, methacrylic acid, (anhydride) phthalic acid, (anhydride) maleic acid, (anhydride) itaconic acid, etc. Also, acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride, acrylamide-2-methylpropanesulfonic acid and its sodium salt, etc. Furthermore, ethyl vinyl ether, butyl vinyl ether, N-vinylpyrrolidone, vinyl chloride, vinyl bromide, vinyl fluoride, vinylidene chloride, vinylidene fluoride, tetrafluoroethylene, sodium vinylsulfonate, sodium allylsulfonate, etc. In addition, terminally modified polyvinyl alcohols obtained by copolymerizing vinyl ester monomers such as vinyl acetate with ethylene in the presence of thiol compounds such as thiol acetate and mercaptopropionic acid, and then saponifying the mixture, can also be used.

[0032] In one embodiment of the present invention, the polyvinyl acetal resin preferably has a glass transition temperature (Tg) of 60°C or lower. This ensures adhesion between the composition (conductive paste) containing the polyvinyl acetal resin and the ceramic green sheet. The preferred lower limit of the glass transition temperature is 25°C, a more preferred lower limit is 30°C, a preferred upper limit is 58°C, and a more preferred upper limit is 55°C. The above glass transition temperature can be measured, for example, using a differential scanning calorimeter (DSC).

[0033] The above glass transition temperature can be adjusted by the method and reaction conditions of the acetalization reaction when producing the polyvinyl acetal resin, the degree of polymerization of the polyvinyl acetal resin, the amount of hydroxyl groups, the amount of acetal groups, the amount of acetyl groups, the structure of the acetal unit (number of carbon atoms in the alkyl group), the type and content of the modifying group, etc.

[0034] Methods for producing the above-mentioned polyvinyl acetal resin include acetalizing polyvinyl alcohol using an aldehyde, and acetalizing a polyvinyl acetal resin having acetal units represented by formula (1) using an aldehyde having 5 to 21 carbon atoms. In particular, it is preferable to use a method in which polyvinyl alcohol is acetalized using at least one aldehyde having 5 to 21 carbon atoms. By using such a production method, the viscosity and glass transition temperature can be adjusted.

[0035] In the method of acetalizing the above-mentioned polyvinyl alcohol using at least one aldehyde having 5 to 21 carbon atoms, examples include preparing aldehydes with different carbon number configurations and then introducing acetal units having multiple alkyl groups with different carbon number configurations by acetalization. When producing the above-mentioned polyvinyl acetal resin, acetalization may be carried out in the presence of a dispersant. More specifically, one method is to introduce the acetal unit represented by formula (1) by acetalizing polyvinyl alcohol that does not have the acetal unit represented by formula (1) with a predetermined aldehyde.

[0036] The above polyvinyl alcohol can be obtained, for example, by saponifying a vinyl ester polymer. Examples of vinyl esters include vinyl formate, vinyl acetate, vinyl propionate, and vinyl pivalate. Among these, vinyl acetate is preferred from an economic standpoint.

[0037] The polyvinyl alcohol resin described above preferably has a degree of saponification of 85 mol% or more. The degree of saponification is more preferably 90 mol% to 99.9 mol%, and even more preferably 95 mol% to 99.4 mol%. That is, the degree of saponification is preferably 90 to 99.9 mol%, and more preferably 95 to 99.4 mol%.

[0038] In the method of reacting the polyvinyl alcohol described above with an aldehyde having 5 to 21 carbon atoms, the aldehyde used in the acetalization reaction is not particularly limited, and examples include linear aliphatic aldehydes and branched aliphatic aldehydes having 5 to 21 carbon atoms. Examples of aliphatic aldehydes having 5 to 21 carbon atoms include baleraldehyde, hexylaldehyde, 2-ethylbutyraldehyde, 2-ethylhexylaldehyde, heptylaldehyde, octylaldehyde, nonylaldehyde, decylaldehyde, undecylaldehyde, dodecylaldehyde, tridecylaldehyde, tetradecylaldehyde, pentadecylaldehyde, hexadecylaldehyde, heptadecylaldehyde, octadecylaldehyde, eicosylaldehyde, heneicosylaldehyde, trimethylhexylaldehyde, methyloctylacetaldehyde, and methylnonylacetaldehyde. These aldehydes may be used individually or in combination of two or more. Particularly preferred is the combination of an aldehyde having 5 to 21 carbon atoms and an aldehyde having 4 or fewer carbon atoms. Among these, acetaldehyde, butyraldehyde, decylaldehyde, and heptaldehyde are preferred aldehydes.

[0039] The amount of aldehyde added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, it is preferable to add 50 mol% to 120 mol%, more preferably 55 mol% to 110 mol%, of 100 mol% of polyvinyl alcohol, as this allows the acetalization reaction to proceed efficiently and makes it easier to remove unreacted aldehydes. That is, the amount of aldehyde added is preferably 50 to 120 mol%, and more preferably 55 to 110 mol%.

[0040] In the acetalization step described above, in addition to the aldehyde having 5 to 21 carbon atoms, an aldehyde having a cyclic aliphatic group or an aromatic group may also be used. Examples of aldehydes having an aromatic group include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde.

[0041] In the acetalization process described above, if an aldehyde with 5 or more carbon atoms is included, a dispersant may or may not be used, but it is preferable to use a dispersant. By using a dispersant in the acetalization process described above, the solvent solubility of the polyvinyl acetal resin can be improved. Furthermore, in the acetalization step described above, it is preferable to use a method in which the polyvinyl acetal resin precipitates during the acetalization reaction (precipitation method), compared with a method in which the reaction is carried out with the polyvinyl acetal resin dissolved (dissolution method). Furthermore, when acetalization is performed using the above dispersant, it is preferable to use the above precipitation method. When using the above dispersant, the amount of dispersant added is preferably 1.5 parts by weight or more and 10 parts by weight or less, and more preferably 3 parts by weight or more and 8 parts by weight or less, per 100 parts by weight of polyvinyl alcohol resin.

[0042] Examples of the above-mentioned dispersants include sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, polyethylene glycol, polyvinyl alcohol, colloidal silica, polyoxyethylene polyoxypropylene cetyl ether, and polyoxyethylene polyoxypropylene lauryl ether. These dispersants may be used individually or in combination of two or more types. Among these, sodium dodecylbenzenesulfonate and polyoxyethylene polyoxypropylene cetyl ether are preferred.

[0043] The above acetalization reaction is preferably carried out in the presence of an acid catalyst. Examples of the acid catalysts mentioned above include mineral acids, carboxylic acids, and sulfonic acids. Examples of the above-mentioned mineral acids include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the carboxylic acids mentioned above include formic acid, acetic acid, and propionic acid. Examples of the above-mentioned sulfonic acids include p-toluenesulfonic acid, methanesulfonic acid, ethanesulfonic acid, and benzenesulfonic acid. These acid catalysts may be used individually or in combination of two or more. Among them, p-toluenesulfonic acid and hydrochloric acid are preferred.

[0044] The temperature at which the above-mentioned aldehyde is added (aldehyde addition temperature) is preferably 5°C or higher, more preferably 10°C or higher, even more preferably 12°C or higher, preferably 75°C or lower, and more preferably 70°C or lower. Furthermore, the temperature at which the catalyst is added is preferably between 10°C and 50°C, and more preferably between 12°C and 20°C. By adding the catalyst within the above range, the solvent solubility of the polyvinyl acetal resin can be improved. The retention time in the above acetalization reaction is preferably 0.5 hours or more and 5 hours or less, and more preferably 1 hour or more and 3 hours or less. Furthermore, the holding temperature in the above acetalization reaction is preferably 0°C or higher and 65°C or lower, more preferably 5°C or higher and 60°C or lower, and even more preferably 12°C or higher and 48°C or lower. In addition, in the above acetalization reaction, it is preferable to perform the holding reaction at a low temperature, then raise the temperature and perform the holding reaction at a high temperature. When performing the holding reaction at a high temperature, the holding temperature is preferably 35°C or higher and 49°C or lower, and more preferably 40°C or higher and 47°C or lower. By keeping the holding time in the above acetalization reaction within the above temperature range, the solvent solubility of the polyvinyl acetal resin can be improved.

[0045] Applications of the polyvinyl acetal resin according to one embodiment of the present invention include, for example, binders and dispersants for conductive pastes, battery electrodes, secondary battery electrodes, etc., modifiers for adhesives based on epoxy resins, phenolic resins, etc., and binders for ceramic green sheets. In particular, when the polyvinyl acetal resin according to one embodiment of the present invention is used as a conductive paste, it exhibits excellent solubility in low-polarity solvents, can suppress sheet attack on the ceramic green sheet, and can improve the surface roughness of the conductive layer.

[0046] A conductive paste containing a polyvinyl acetal resin according to one aspect of the present invention, an organic solvent, a conductive powder, and a dispersion improver is also one aspect of the present invention.

[0047] The organic solvent mentioned above can be an organic solvent commonly used in conductive pastes. Examples of the above organic solvents include terpineol derivatives such as dihydroterpineol, terpinyl acetate, isovonyl acetate, dihydroterpinyl acetate, dihydroterpinyl methyl ether, and terpinyl methyl ether, hydrocarbon solvents such as mineral spirits, and ethers and esters such as dipropylene glycol monomethyl ether and dipropylene glycol monomethyl ether acetate. Among these, dihydroterpineol and dihydroterpinyl acetate are preferred. These organic solvents may be used individually or in combination of two or more.

[0048] The amount of the above organic solvent is not particularly limited, but a preferred lower limit is 100 parts by weight and a preferred upper limit is 10,000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin. When the amount of the above organic solvent is 100 parts by weight or more, the viscosity of the conductive paste can be set within a suitable range and the printability can be improved. When the amount of the above organic solvent is 10,000 parts by weight or less, the performance of the above polyvinyl acetal resin can be fully exhibited in the conductive paste. A more preferred lower limit for the amount of the above organic solvent relative to 100 parts by weight of the polyvinyl acetal resin is 200 parts by weight and a more preferred upper limit is 5,000 parts by weight.

[0049] The conductive powders mentioned above are not particularly limited and include, for example, powders made of nickel, aluminum, silver, copper, and alloys thereof. These conductive powders may be used individually or in combination of two or more. Among these, nickel is preferred because of its excellent conductivity.

[0050] The average particle size of the conductive powder is preferably 50 to 300 nm, and its shape is preferably approximately spherical. An average particle size of 50 nm or more allows for a suitable specific surface area of ​​the conductive powder, thereby improving its dispersibility. An average particle size of 300 nm or less improves the surface smoothness after printing. Note that "approximately spherical" includes not only perfectly spherical particles but also particles with a shape close to spherical.

[0051] The amount of conductive powder used is not particularly limited, but a preferred lower limit is 100 parts by weight and a preferred upper limit is 10,000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin. If the amount of conductive powder blended is 100 parts by weight or more, the density of the conductive powder in the conductive paste can be kept within a sufficient range, resulting in excellent conductivity. If the amount of conductive powder blended is 10,000 parts by weight or less, the dispersibility of the conductive powder in the conductive paste can be improved, resulting in excellent printability. The amount of conductive powder blended is preferably 200 parts by weight and 5000 parts by weight relative to 100 parts by weight of the polyvinyl acetal resin.

[0052] Preferably, the conductive paste described above further contains ceramic powder in addition to the conductive powder. Including ceramic powder makes it easier to match the shrinkage behavior of the conductive powder during firing with that of the ceramic green sheet. The ceramic powder is not particularly limited, but barium titanate used in green sheets is preferred. The average particle size of the ceramic powder is not particularly limited, but it is preferably smaller than the average particle size of the conductive powder, and specifically, it is preferably 30 nm to 200 nm.

[0053] The conductive paste described above may appropriately contain plasticizers, lubricants, antistatic agents, dispersion enhancers, surfactants, etc., to the extent that it does not impair the effects of the present invention.

[0054] Examples of the above-mentioned plasticizers include phthalate diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, and alkylene glycol diesters such as triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethyl butyrate, tetraethylene glycol-di-2-ethyl butyrate, tetraethylene glycol-di-heptanoate, and triethylene glycol-di-heptanoate.

[0055] The above-mentioned dispersion enhancer is not particularly limited, but for example, fatty acids, aliphatic amines, alkanolamides, and phosphate esters are preferred. Silane coupling agents and the like may also be included. The above fatty acids are not particularly limited and include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, and coconut fatty acid; and unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, beef tallow fatty acid, and hydrogenated castor fatty acid. Among these, lauric acid, stearic acid, and oleic acid are preferred. The above-mentioned aliphatic amines are not particularly limited and include, for example, laurylamine, myristylamine, cetylamine, stearylamine, oleylamine, alkyl(coconut)amine, alkyl(hydrogenated beef tallow)amine, alkyl(beef tallow)amine, alkyl(soybean)amine, etc. The above-mentioned alkanolamides are not particularly limited and include, for example, coconut fatty acid diethanolamide, beef tallow fatty acid diethanolamide, lauric acid diethanolamide, oleic acid diethanolamide, etc. The above-mentioned phosphate esters are not particularly limited, and examples include polyoxyethylene alkyl ether phosphate esters and polyoxyethylene alkyl allyl ether phosphate esters.

[0056] The method for producing the above-mentioned conductive paste is not particularly limited, and examples include mixing the above-mentioned polyvinyl acetal resin, the above-mentioned conductive powder, the above-mentioned organic solvent, and various additives added as needed using various mixers such as a ball mill, a blender mill, or a three-roll mill.

[0057] A multilayer ceramic capacitor can be obtained by applying the above-mentioned conductive paste onto a ceramic green sheet using a printing process, stacking multiple sheets, heating and pressing them together to create a laminate, then degreasing and firing to form a ceramic sintered body, and finally forming external electrodes on the end faces of the ceramic sintered body. The above-mentioned printing process can include screen printing, die coating, gravure offset, etc. Such a multilayer ceramic capacitor is also one of the present inventions. Furthermore, the polyvinyl acetal resin or the conductive paste according to one embodiment of the present invention can also be suitably used as a multilayer ceramic capacitor. Furthermore, a multilayer ceramic capacitor according to one aspect of the present invention can be manufactured by performing the steps of: applying a conductive paste according to one aspect of the present invention onto a ceramic green sheet; stacking multiple ceramic green sheets and heating and pressing them together to produce a laminate; degreasing and firing to produce a ceramic sintered body; and forming external electrodes on the end faces of the ceramic sintered body. [Effects of the Invention]

[0058] According to the present invention, it is possible to provide a polyvinyl acetal resin that can form a conductive layer with excellent solvent solubility and low surface roughness while preventing sheet attack, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin. [Modes for carrying out the invention]

[0059] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0060] (Example 1) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. The solution was cooled to 65°C, and 80 g of n-butyraldehyde and 85 g of n-decylaldehyde were added. Then, the solution was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid, diluted in 180 g of pure water, was added. The solution temperature was maintained at 15°C for 1 hour to allow the acetalization reaction to proceed, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was continued for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. The solution was then neutralized, washed with water, and dried by conventional methods to obtain a polyvinyl acetal resin (long-chain alkyl modified) powder. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 1. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0061] (Example 2) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 98.7 mol% and an average degree of polymerization of 1100, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. The solution was cooled to 65°C, and 75 g of n-butyraldehyde and 80 g of n-decylaldehyde were added. Then, the solution was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid, diluted in 180 g of pure water, was added. The solution temperature was maintained at 15°C for 1 hour to allow the acetalization reaction to proceed, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was continued for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. The solution was then neutralized, washed with water, and dried by conventional methods to obtain a powder of polyvinyl acetal resin (long-chain alkyl modified). The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 1. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0062] (Example 3) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. The solution was cooled to 65°C, and 180g of n-decylaldehyde was added. Then, it was cooled to 15°C, and 20g of 35% by mass hydrochloric acid, diluted in 180g of pure water, was added. The solution temperature was maintained at 15°C for 1 hour to allow the acetalization reaction to proceed, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was continued for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin (long-chain alkyl modified) powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 1. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 = (CH2)8CH3]

[0063] (Example 4) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 98.9 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. The solution was cooled to 65°C, and 80 g of n-butyraldehyde and 85 g of n-heptaldehyde were added. Then, the solution was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid, diluted in 180 g of pure water, was added. The solution temperature was maintained at 15°C for 1 hour to allow the acetalization reaction to proceed, and the reaction product was precipitated. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was continued for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. The solution was then neutralized, washed with water, and dried by conventional methods to obtain a polyvinyl acetal resin (long-chain alkyl modified) powder. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 1. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0064] (Example 5) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. This solution was cooled to 65°C, and 87 g of n-butyraldehyde and 75 g of n-decylaldehyde were added. Then, it was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid was added, diluted with 180 g of pure water. The solution temperature was maintained at 15°C for 1 hour to carry out the acetalization reaction and precipitate the reaction product. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was carried out for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a powder of polyvinyl acetal resin (long-chain alkyl modified) was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 1. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0065] (Example 6) (Preparation of polyvinyl acetal resin) 150 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700, and 13.5 g of Unisafe 10P-8 (polyoxyethylene polyoxypropylene cetyl ether, manufactured by NOF Corporation), diluted with pure water to a concentration of 20% by mass as a dispersant, were added to 1600 g of pure water and stirred at 90°C for 2 hours to dissolve. This solution was cooled to 65°C, and 100 g of n-butyraldehyde and 30 g of n-decylaldehyde were added. Then, it was cooled to 15°C, and 20 g of 35% by mass hydrochloric acid was added, diluted with 180 g of pure water. The solution temperature was maintained at 15°C for 1 hour to carry out the acetalization reaction and precipitate the reaction product. After 1 hour of the acetalization reaction, 13.5 g of 20% by mass sodium dodecylbenzenesulfonate (SDBS) dissolved in pure water was added, and the acetalization reaction was carried out for another hour. Next, the temperature was raised to 45°C at a rate of 2-3°C / 5 minutes, and the solution temperature was maintained at 45°C for 3 hours to complete the reaction. After neutralization, washing with water, and drying by conventional methods, a powder of polyvinyl acetal resin (long-chain alkyl modified) was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total acetal group content (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 1. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0066] (Comparative Example 1) (Preparation of polyvinyl acetal resin) 160 g of carboxylic acid-modified polyvinyl alcohol (itaconic acid modified, carboxylic acid modification amount 0.5 mol%) with a saponification degree of 98.2 mol% and an average degree of polymerization of 800 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 20 g of acetaldehyde and 110 g of n-butyraldehyde were added to carry out the acetalization reaction, and the reaction product was precipitated. Next, the solution temperature was maintained at 50°C for 4 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (chloroform), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of carboxylic acid modification were measured. Furthermore, the total amount of acetal groups (sum of the content of each acetal unit) was calculated from the measured values. Note that the content of each acetal unit is as follows: 13 The results were quantified using 1C-NMR. The results are shown in Table 2. The acetal units were acetacetal units and butyral units.

[0067] (Comparative Example 2) (Preparation of polyvinyl acetal resin) 160 g of polyvinyl alcohol resin with a saponification degree of 95.0 mol% and an average degree of polymerization of 800 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 140 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 50°C for 4 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in DMSO-D6 (didimethyl sulfoxide), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of alkylene oxide modification were measured. The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.

[0068] (Comparative Example 3) (Preparation of polyvinyl acetal resin) 160 g of carboxylic acid-modified polyvinyl alcohol (itaconic acid modified, carboxylic acid modification amount 0.2 mol%) with a saponification degree of 98.4 mol% and an average degree of polymerization of 1700 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 140 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 50°C for 4 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (chloroform), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of carboxylic acid modification were measured. Furthermore, the total amount of acetal groups (sum of the content of each acetal unit) was calculated from the measured values. Note that the content of each acetal unit is as follows: 13 The results were quantified using 1C-NMR. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.

[0069] (Comparative Example 4) (Preparation of polyvinyl acetal resin) 160 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 55 g of n-butyraldehyde and 60 g of n-heptaldehyde were added to carry out the acetalization reaction, and the reaction product was precipitated. Next, the solution temperature was maintained at 50°C for 3 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0070] (Comparative Example 5) (Preparation of polyvinyl acetal resin) 160 g of ethylene oxide-modified polyvinyl alcohol resin (ethylene oxide modification amount 1.5 mol%) with a saponification degree of 99.0 mol% and an average degree of polymerization of 1200 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 140 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 50°C for 3 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in DMSO-D6 (didimethyl sulfoxide), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of ethylene oxide modification were measured. The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.

[0071] (Comparative Example 6) (Preparation of polyvinyl acetal resin) 160 g of ethylene-modified polyvinyl alcohol (ethylene modification amount 4.0 mol%) with a saponification degree of 98.4 mol% and an average degree of polymerization of 1700 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 140 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 50°C for 4 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of ethylene modification were measured. The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.

[0072] (Comparative Example 7) (Preparation of polyvinyl acetal resin) 160 g of polyvinyl alcohol resin with a degree of saponification of 98.9 mol% and an average degree of polymerization of 800 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 160 g of n-butyraldehyde was added to carry out the acetalization reaction, precipitating the reaction product. Next, the solution temperature was maintained at 50°C for 6 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in DMSO-D6 (didimethyl sulfoxide), 1 Using 1H-NMR (nuclear magnetic resonance spectroscopy), the content of each acetal unit, the amount of acetyl groups, the amount of hydroxyl groups, and the amount of alkylene oxide modification were measured. The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. The acetal unit was equivalent to the butyral unit.

[0073] (Comparative Example 8) (Preparation of polyvinyl acetal resin) 160 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 81 g of n-butyraldehyde and 23 g of n-heptaldehyde were added to carry out the acetalization reaction, and the reaction product was precipitated. Next, the solution temperature was maintained at 50°C for 3 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13 The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)5CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0074] (Comparative Example 9) (Preparation of polyvinyl acetal resin) 160 g of polyvinyl alcohol with a saponification degree of 99.0 mol% and an average degree of polymerization of 1700 was added to 1700 g of pure water and dissolved by stirring at 90°C for 2 hours. The solution was cooled to 40°C, and 120 g of 35% by mass hydrochloric acid was added. Then, the solution was cooled to 10°C, and 61 g of n-butyraldehyde and 58 g of n-decylaldehyde were added to carry out the acetalization reaction, and the reaction product was precipitated. Next, the solution temperature was maintained at 50°C for 3 hours to complete the reaction, and after neutralization, washing with water, and drying by conventional methods, a polyvinyl acetal resin powder was obtained. The obtained polyvinyl acetal resin is dissolved in CDCl3 (deuterated chloroform), 1 H-NMR and 13The content of each acetal unit, acetyl group, and hydroxyl group was measured using 1C-NMR (nuclear magnetic resonance spectroscopy). The total amount of acetal groups (sum of the content of each acetal unit) was also calculated from the measured values. The results are shown in Table 2. Note that the content of each acetal unit is as follows: 13 Quantitative analysis was performed using 1C-NMR. Note that the acetal unit is a constituent unit represented by the above formula (1) [R 1 =(CH2)8CH3] and the constituent unit represented by the above formula (2) [R 2 =(CH2)2CH3]

[0075] <Rating> The obtained polyvinyl acetal resin was evaluated as follows. (1) Solubility parameters 1 H-NMR and 13 Based on the results of 1C-NMR (nuclear magnetic resonance spectroscopy), the solubility parameter (SP value, unit: cal / cm³) of polyvinyl acetal resin was determined according to the Fedors method. 3 ) was calculated. Furthermore, from the solubility parameter [X] and the content of the constituent unit represented by the above formula (1) [Y], "Y 2 / X (Unit: [mol%]) 2 ·cm 3 The calculation was performed using ` / cal`.

[0076] (2) Solvent solubility A 30g solution was prepared in a sealed glass container by mixing polyvinyl acetal resin and dihydroterpinyl acetate to a concentration of 10% by mass. The solution was stirred at room temperature for 1 hour using a stirrer, then heated to 90°C using a hot stirrer and stirring was continued. The solution state was visually inspected and evaluated according to the following criteria. Dissolution was confirmed by visually observing the solution in a transparent glass container under a white background and confirming that no solid matter remained (complete dissolution). Furthermore, if the evaluation for "solvent solubility" is "C," subsequent evaluations cannot be performed, so the evaluation results for "sheet attack evaluation" and "surface roughness" were set to "- (unable to evaluate)."

[0077] A: Completely dissolves in less than 3 hours B: Completely dissolves in 3 hours to less than 7 hours. C: Even after more than 7 hours, some residue remains.

[0078] (3) Evaluation of sheet attack on ceramic green sheet (Preparation of inorganic dispersions) One part by weight of polyvinyl acetal resin (BL-1, manufactured by Sekisui Chemical Co., Ltd.) was added to a mixed solvent of 20 parts by weight of toluene and 20 parts by weight of ethanol, and dissolved by stirring. Next, 100 parts by weight of barium titanate powder (BT01, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the resulting solution, and an inorganic dispersion was prepared by stirring for 180 minutes using a bead mill (Ready Mill, manufactured by AIMEX Co., Ltd.).

[0079] (Preparation of resin solution) A resin solution was prepared by adding 8 parts by weight of polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., BH-3) and 2 parts by weight of DOP to a mixed solvent of 45 parts by weight of ethanol and 45 parts by weight of toluene, and stirring to dissolve.

[0080] (Preparation of ceramic green sheets) A resin solution was added to the obtained inorganic dispersion and stirred in a bead mill for 90 minutes to obtain a composition for ceramic green sheets. The obtained ceramic green sheet composition was coated onto a PET film that had been released using a coater to a thickness of 20 μm after drying, and then heated and dried to produce a ceramic green sheet.

[0081] (Seat attack performance evaluation) Two parts by weight of the obtained polyvinyl acetal resin and 98 parts by weight of 2-ethylhexyl acetate were added and stirred to dissolve, thereby obtaining a polyvinyl acetal resin composition. The obtained ceramic green sheet was cut into 5cm x 5cm squares. Then, 70 μL of the above polyvinyl acetal resin composition at 23°C was dropped onto the test piece, and the time of dropping was set to 0. After that, the ceramic green sheet was visually observed, and the time until wrinkles formed on the ceramic green sheet was measured and judged according to the evaluation criteria below. Note that when visually observing the surface of the ceramic green sheet from the side on which the polyvinyl acetal resin composition was dropped, it was determined that wrinkles had formed if unevenness or linear deformation was visible. The longer the time until wrinkles form, the better the sheet attack performance.

[0082] AA:120s or more A: 100 seconds or more, less than 120 seconds B: 80s or more, less than 100s C: Less than 80s

[0083] (4) Surface roughness A resin solution was obtained by dissolving 10 parts by weight of the obtained polyvinyl acetal resin in 90 parts by weight of dihydroterpinyl acetate. After mixing 180 parts by weight of nickel powder as conductive powder, 50 parts by weight of dihydroterpinyl acetate, and 0.1 parts by weight of oleic acid as a dispersion improver, the obtained resin solution was mixed and dispersed using a three-roll machine to obtain a conductive paste. 0.5 g of the obtained conductive paste was coated onto a glass slide using a bar coater and dried on a hot plate at 120°C for 5 minutes. Thereafter, the surface roughness Ra was measured using a contact surface roughness meter according to JIS B 0601 (1994), and the surface roughness of the conductive layer was evaluated according to the following criteria.

[0084] AA:Ra is less than 35nm A: Ra is 35nm or higher, and less than 45nm. B:Ra is 45nm or higher and less than 55nm. C:Ra is 55nm or higher

[0085] [Table 1]

[0086] [Table 2] [Industrial applicability]

[0087] According to the present invention, it is possible to provide a polyvinyl acetal resin that can form a conductive layer with excellent solvent solubility and low surface roughness while preventing sheet attack, as well as a conductive paste and a multilayer ceramic capacitor using the polyvinyl acetal resin.

Claims

1. The solubility parameter calculated according to Fedors' method is 10.25 or less, and it has a constituent unit represented by the following formula (1), and R in the following formula (1) 1 A polyvinyl acetal resin in which the hydrocarbon group has 4 to 20 carbon atoms. 【Chemistry 1】

2. If the solubility parameter is X and the content of the constituent unit represented by formula (1) is Y, then Y 2 The polyvinyl acetal resin according to claim 1, wherein / X is 65 or more and 900 or less, and the average degree of polymerization is less than 2300.

3. The polyvinyl acetal resin according to claim 1 or 2, wherein the amount of hydroxyl groups is 8 mol% or more and 25 mol% or less.

4. R in formula (1) 1 The polyvinyl acetal resin according to claim 1 or 2, wherein the hydrocarbon group is linear and has 6 to 20 carbon atoms.

5. The polyvinyl acetal resin according to claim 1 or 2, wherein the content of the constituent unit represented by formula (1) is 5 mol% or more and 80 mol% or less.

6. The polyvinyl acetal resin according to claim 1 or 2, wherein the total amount of acetal groups is 79 mol% or more.

7. A conductive paste comprising the polyvinyl acetal resin according to claim 1 or 2, an organic solvent, a conductive powder, and a dispersion improver.

8. A multilayer ceramic capacitor comprising the conductive paste described in claim 7.

Citation Information

Patent Citations

  • Modified polyvinyl acetal resin, coating paste, conductive paste, and ceramic paste

    JP2008285590A

  • Conductive paste

    JP2017228780A